2022
DOI: 10.1155/2022/9661506
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Microscope Combined with Wechat Smart Platform on Clinical Efficacy and Gastrointestinal Function of Patients with Cholecystolithiasis Combined with Common Bile Duct Stones

Abstract: To explore the clinical efficacy of microscope combined with Wechat smart platform in patients with cholecystolithiasis and choledocholithiasis, this paper proposes the effect of microscope combined with Wechat smart platform intervention after laparoscopic lithotomy and choledocholithotomy on the clinical efficacy and gastrointestinal function of patients with cholecystolithiasis combined with choledocholithiasis. From February 2018 to March 2019, 78 patients with gastric cancer were selected by our clinic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%